Testing the PEGR investment strategy : Empirical evidence from the Nordic stock market - Österman, Akseli (My University, 2023)
Traditional and widely utilized financial theories and asset-pricing models generally rely on assumptions and restrictions of the market and investors’ behavioral characteristics. One of the essential assumptions is that the information is free and equally available for all market participants, and that in equilibrium conditions the security prices fully reflect the information available. Thus, in theory the securities are always correctly valued, and higher returns should only be achievable by increasing the risk simultaneously. However, the validity of the traditional theories and asset-pricing models have since been criticized, and various research have provided evidence of the existence of market anomalies. The anomalies suggest that it is, in fact, possible for investors to achieve abnormal returns from investment strategies and predictive patterns by investing in certain assets with specific characteristics or risk factors. Previous empirical evidence of the price-to-earnings-to-growth (PEG) ratio related investment strategies argues that generally the lowest PEG-ratio securities have outperformed the higher PEG-ratio securities, also indicating that the low PEG investment strategy has some anomalous characteristics beneficial for the investors. This research pursues to examine whether abnormal stock returns can be achieved on the Nordic stock market by investing in low PEG-ratio securities. Generally, in previous related research the PEG-ratios have been defined with analyst estimates of the earnings growth rates. This research, however, provides further evidence of an alternative log-linear earnings growth rate estimation model initially presented by Wang et al. (2020). The log-linear method does not have similar constraints and deficiencies as the analyst estimates, and thus provides a functional approach for the PEG-related analysis on smaller markets. Three different portfolio types are annually composed, based on the companies’ PEG-ratios and main operating industries, pursuing to provide further evidence of the companies’ PEG-specific characteristics in different industries. The analysed portfolios are equally weighted and constructed of companies publicly listed on the OMX Nordic All-Share Index during years 2012-2022. The analyses are being conducted by utilizing the Fama-French three-factor regression model, and the robustness of the results is tested with the Carhart four-factor model, and with the alternative log-linear earnings growth rate estimation methods provided in this research. The results indicated that the second lowest PEG portfolio was the only portfolio achieving excess returns on the market, suggesting that the low PEG investment strategy did not outperform all the higher PEG ratio portfolios on the Nordic stock market in its entirety, which is in contradiction to the previous evidence of the low PEG anomaly. However, the concerning anomaly was remarkably observable withing two individual industry groups, financials and real estate, and health care and utilities. To conclude, the Wang et al. method proved to be a functional tool for evaluating the earnings growth rate estimates of companies, as the method conducted similar PEG characteristics and scale of the PEG values in relation to the previous related research, which generally have been utilizing analyst estimates in defining the PEG-ratios. The alternative estimation methods presented in this research also provided interesting return characteristics, but further research and evidence is still necessary.

Perinteisesti rahoituksessa hyödynnetyt teoriat ja arvopapereiden hinnoittelumallit ovat pohjautuneet vahvoihin oletuksiin markkinoista ja sijoittajien toimintamalleista. Keskeisimmät oletukset teorioiden taustalla liittyy taloudellisen informaation saatavuuteen sekä siihen, että arvopapereiden hinnoittelu teoreettisessa tasapainotilassa perustuu täysin saatavilla olevaan taloudelliseen informaatioon. Tällöin arvopapereiden hinnoittelun tulisi olla aina täysin oikeellinen, ja sijoittajien tulisi voida saavuttaa korkeampia tuottoja ainoastaan korottamalla sijoitustensa riskiä. Tätä on kuitenkin kritisoitu laajalti ja useat tutkimukset ovat jälkeenpäin osoittaneet, että sijoittajat voivat saavuttaa ylituottoja hyödyntämällä havaittuja markkinapoikkeamia, eli anomalioita. Empiiriset tulokset ovat osoittaneet, että matalimman price-to-earnings-to-growth (PEG) -luvun arvopaperit ovat suoriutuneet paremmin kuin korkeamman PEG-luvun arvopaperit, minkä pohjalta voidaan olettaa, että sijoittajien on matalan PEG-luvun sijoitusstrategialla mahdollista saavuttaa poikkeavia ylituottoja markkinoilta. Tämän tutkimuksen tarkoituksena on selvittää, onko matalimman PEG-luvun sijoitusstrategiaa hyödyntämällä mahdollista saavuttaa ylituottoja pohjoismaisilla osakemarkkinoilla. Pääsääntöisesti aikaisemmissa tutkimuksissa PEG-luku on määritetty pohjautuen analyytikoiden estimaatteihin tulevien osinkotuottojen kasvuvauhdista. Tässä tutkimuksessa tulevien osinkotuottojen kasvuvauhti määritetään vaihtoehtoisesti log-lineaarisella menetelmällä, pohjautuen Wang ym. (2020) esittämään estimaatiomalliin. Log-lineaarinen malli soveltuu erityisesti pienemmillä markkinoilla käytettäväksi, sillä se ei sisällä samankaltaisia rajoituksia ja haasteita kuten analyytikoiden asettamat estimaatit. Tutkimuksessa analysoidaan kolmea erityyppistä portfoliomallia, jotka perustuvat määritettyihin PEG-lukuihin ja yritysten pääasiallisiin toimialoihin. Analysoidut portfoliot koostetaan ja tasapainotetaan vuosittain OMX Nordic All-Share indeksissä julkisesti listatuista yrityksistä vuosina 2012–2022. Lopulliset analyysit suoritetaan Fama-French kolmifaktorimallilla. Tulosten jatkuvuutta tarkastellaan Carhartin nelifaktorimallin sekä tässä tutkimuksessa esitettyjen vaihtoehtoisten log-lineaaristen estimaatiomallien tulosten avulla. Tulokset osoittavat, että toiseksi matalimman PEG-luvun portfolio saavutti ainoana portfoliona tilastollisesti merkitsevää ylituottoa koko pohjoismaisilla osakemarkkinoilla mitattuna vuosina 2012–2022. Tulosten pohjalta voidaan siis todeta, että kaikista matalimman PEG-luvun portfolio ei saavuttanut ylituottoja, eikä suoriutunut korkeamman PEG-luvun portfolioita paremmin. Tulokset ovat siis poikkeavia aikaisempiin tutkimustuloksiin verrattuna, missä matalan PEG- luvun anomalia on ollut havaittavissa. Toimialakohtaisessa tarkastelussa kuitenkin osoittautui, että matalimman PEG-luvun portfoliot saavuttivat ylituottoja kahdessa toimialajoukossa – rahoitus- ja kiinteistöalalla, sekä terveydenhuolto- ja yleishyödyllisellä alalla. Wang ym. (2020) esittämä log-lineaarinen estimaatiomalli osoittautui toimivaksi tulevien osinkotuottojen kasvuvauhdin ja PEG-luvun määrityksessä, tuottaen myös aikaisempiin tutkimustuloksiin nähden vertailukelpoisia tuloksia. Tutkimuksessa esitetyt vaihtoehtoiset log-lineaariset estimaatiomallit tarjoavat myös mielenkiintoisia tuloksia sekä tuotto-ominaisuuksia, mutta jatkotutkimukset sekä menetelmien testaukset ovat kuitenkin edelleen tarpeellisia.
Keywords: anomaly, excess returns, growth rate estimate, PEG